Implementation of Jazariyah Book Learning for Language Phonology in Increasing Maharah Qiraah Student - Agung Yusup; Muhammad Sobri; Melfi Armanda Kusuma (al-Afkar, Journal For Islamic Studies, 2026)
This research is needed to improve the quality of students' language phonology in maharah qiraah. This allows students to pronounce letters according to their letter makhrijul and minimize students' mistakes in language phonology. This research is a quantitative study with a type of correlational research and this research is survey-based using a chair. Apart from that, this research also uses preat software version 6.3.09 to analyze errors in students' language phonology. The results in this research show that there is an influence of variable X (Language Phonology based on the Book of Jazariyah) on variable Y (Maharah Qiraah students). The calculated r result of this correlation test is 0.586 > 0.312 and the sig.2-tailed value is 0.001 < 0.05. As stated in the correlation interpretation table. 0.586 is included in the fairly strong correlation category. Then the results of a simple linear regression analysis were obtained by looking at the Anova table, the results of the F count score = 19.837 with a significance level of 0.001 < 0.05, which means that there is an influence of variable X Language Phonology based on the Book of Jazariyah) on variable Y (Maharah Qiraah students). Then the correlation value by looking at the summary model table is 0.343, which means that the magnitude of the implications of using the jazzariyah book as a phonological learning medium for mastering students' maharah qiraah is 34.3 %.